Obstetric Violence as Reproductive Governance in the Dominican Republic. Issue 2 (17th February 2019) - Castro, Arachu; Savage, Virginia
ABSTRACT: A human rights violation, obstetric violence encompasses numerous forms of mistreatment against women giving birth in health care facilities. Based on this framework, we conducted open-ended exit interviews with 43 women who had given birth at either one of the two largest public maternity hospitals in the Dominican Republic. Women's narratives revealed a contrast between scholarly definitions of obstetric violence and their own perceptions of receiving abusive care. Analyzing obstetric violence as a form of reproductive governance and the adaptive preference that ensues helps explain why most women accepted with endurance the poor quality of care that they received.